Molecular insights into novel environmental strains of Klebsiella quasipneumoniae harboring different antimicrobial-resistance genes - Hisham N. Altayb; Hisham N. Altayb; Salman Hosawi; Othman Baothman; Imran Kazmi; Kamel Chaieb; Isam M. Abu Zeid; Hana S. Elbadawi; Bruno Silvester Lopes; Bruno Silvester Lopes; Ehssan Moglad (Frontiers Media S.A., 2023)
IntroductionThe emergence of bacterial pathogens in environmental hosts represents a major risk to public health. This study aimed at characterizing seven novel environmental strains of K. quasipneumoniae using a genomic approach which was misidentified by phenotypic methods in a previous batch of 27 species thought to be K. pneumoniae.MethodsWhole-genome sequencing was performed using the Illumina platform, and the generated raw reads were de novo assembled. Comparative genomic, resistome, virulome, mobilome, and phylogeny were then investigated using dierent bioinformatics tools.ResultsSix strains were identified as K. quasipneumoniae subsp similipneumoniae and one as K. quasipneumoniae subsp. quasipneumoniae. All isolates were resistant to ampicillin, cephalexin, and amoxicillin-clavulanic acid and harbored the fosA, blaOKP types, oqxB, and oqxA genes. One isolate additionally harbored a gene cassettes consisting of blaSHV−1, blaOXA−1, aac(6')-Ib-cr, catB genes. The aminoglycoside-modifying enzyme gene aph(3")-Ia was bracketed by two insertion elements. Plasmid analyses showed that IncFIBK was the most prevalent plasmid, circulating in six isolates, while one isolate exhibited seven different plasmids. The isolates have virulence genes responsible for capsule formation, lipopolysaccharide, iron uptake aerobactin (iutA), salmochelins (iroE, iroN), enterobactin siderophore, adherence, and biofilm formation (mrkA, mrkB, mrkC, mrkD, mrkF, and mrkH).ConclusionOur study highlights the ecology and transmission of K. quasipneumoniae (which have the ability to disseminate to other environmental sources including animals) outside the clinical setting and the contribution of water, vegetables, and table surfaces as potential reservoirs of farm-to-fork transmission of disease via local markets in Khartoum, Sudan.